(UN)Bundling Public-Private Partnership Contracts In The Water Sector : Competition In Auctions And Economies of Scale In Operation - Iimi, Atsushi (The World Bank, 2008)
In public-private partnership transactions in the water sector, one of the alleged concerns is that there is little market competition at the auction stage. This paper casts light on a tradeoff between the competition effect at the auction level and potential economies of scale in service operation. If the authorities design a large-scale public-private partnership water transaction, it is expected to exploit operational scale economies. But the competition effect may have to be sacrificed. The paper shows a risk that the selection of the contract size could be a very restrictive condition that excludes many prospective bidders. Moreover, the paper quantifies the optimal size of public-private partnership contracts in the sector by estimating a cost function. The analysis shows that economies of scale exist but tend to diminish quickly as production increases. When the amount of water sold exceeds about 40 million m3, the statistical significance of economies of scale disappears. And there is no rationale for auctioning the water operation with annual water delivery of more than 400 million m3 under a single contract